Latin America and the Caribbean : policies to improve linkages with the global economy (UN. ECLAC SantiagoCL, 1995)
Discusses three interrelated types of policies, namely, trade policy, micro- and meso-economic policy in support of production systems, and macroeconomic policy, with specific emphasis on financial flows.
Bibliography: p. 293-308